Pengaruh Profitabilitas, Ukuran Perusahaan, Kepemilikan Institusional, dan Komite Audit terhadap Ketepatan Waktu Pelaporan Keuangan dengan Opini Auditor sebagai Variabel Moderasi pada Perusahaan Sektor Consumer Non-Cyclicals yang Terdaftar di Bursa Efek Indonesia - Halawa, Marliyoni; Ginting, Rasinta Ria; Simorangkir, Enda Noviyanti; Helman, Helman; Hutagalung, Galumbang (Universitas Nahdlatul Ulama Surabaya, 2024)
The aim of this research is to determine the effect of profitability, company size,institutional ownership, and audit committee on the timeliness of financial reporting with auditor opinion as a moderating variable. The population of this research is 113 non-cyclical consumersector companies listed on the Indonesia Stock Exchange for the period 2018 to 2022. Thesampling method used in this research is purposive sampling, so that 35 sample companies wereobtained during 5 years of observation (2018 - 2022) with 175 unit of analysis. Data wereanalyzed using the SmartPLS data processing program version 4.0. The research results show thatprofitability has no effect on the timeliness of financial reporting. Company size and institutionalownership influence the timeliness of financial reporting. The audit committee has no effect on thetimeliness of financial reporting. With moderation, profitability, company size and institutionalownership are able to be moderated by the auditor's opinion on the timeliness of financialreporting, while the audit committee is not able to be moderated by the auditor's opinion on thetimeliness of financial reporting.